Testing a community developed training protocol for an evidence-based treatment. (June 2022) - Quetsch, Lauren B.; Herschell, Amy D.; Kolko, David; Liebsack, Brittany K.; Carroll, Regina A.
Abstract: The implementation of evidence-based treatments (EBTs) in community behavioral health settings is a recommended practice, yet training experienced by community-based clinicians may require novel and creative training methods. The current study focused on creating a training protocol for Alternative for Families: a Cognitive-Behavioral Therapy from both evidence-based foundations and community-based agency feedback to promote better EBT integration into agencies. Twenty-four clinicians from three agencies were trained using a community-informed training protocol. Outcomes for clinician-reports of organizational functioning, self-reports of skill and knowledge, and observational single-subject data of clinician skills were assessed. Minimal improvements were found for clinician skills across self-report and observations. More research on tailoring trainings to meet needs of community agencies and clinicians should be explored to determine best practice in wide-scale implementation efforts. Highlights: A cognitive-behavior therapy training was developed with community-based agencies. Clinician self-reported knowledge and skill use did not change after the training. Clinicians' attitudes toward the treatment also did not change after the training. Single-subject audio data was recorded and analyzed to measure clinician skills. Clinicians were best at "establishing an agenda" and "assigning home practice".